Water Security During the Covid-19 Pandemic in Sentul City - edward alfin (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2021)
This research was conducted to determine the state of the water in Sentul City. The method used in this research is observation, interview and water measurement. The results showed that Sentul area has five soil classifications, namely typic hapludult, typic dystropept, oxic dystropept, typic hemipropept and aquic dystropept. The Sentul area has a undulating, hilly and mountainous topography with an altitude between 200 m-750 m above sea level. The Sentul area has 2 rivers, namely the Cikeas River and the Citeureup River. It was found that the chemical parameters for BOD5 and COD exceeded the established thresholds. The physical and microbiological parameters are still below the established threshold. Sentul City's water needs are currently at 5,162,500 liters / day. The water requirement is supplied by PDAM Tirta Kahuripan of 17,280 m3 / day. This situation makes Sentul City a surplus of water. The water surplus made Sentul City have water resistance during the Covid-19 pandemic.